Leadership Style, Work Environment, and Compensation as Determinants of Employee Performance in the Primary Tax Service Office Surabaya Pabean Cantikan - Yohana, Febrita; Purwanto, Purwanto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the combined effects of Leadership Style, Work Environment, and Compensation on the performance of employees at the Primary Tax Service Office (KPP) Pratama Surabaya Pabean Cantikan, positioning human capital as a pivotal element in organizational achievement. The research involved all 79 employees in 2025 using a total sampling approach, with data obtained from questionnaires, interviews, direct observations, and organizational documentation. Multiple linear regression analysis, alongside tests for normality, reliability, multicollinearity, and heteroscedasticity, ensured the robustness of findings. Results demonstrate that leadership practices, employing both transactional and transformational techniques, enhance motivation, provide direction, and recognize staff contributions, improving overall performance. A conducive work environment with ample space, ergonomic setups, and supportive co-worker interactions reduces stress and enables employees to focus, increasing productivity. Compensation, including financial incentives and essential non-monetary benefits such as fieldwork vehicles, technology, and communication tools, further facilitates efficient task completion. The integration of these factors has a significant positive impact on employee performance, emphasizing that a holistic HR management approach is critical in public sector settings. Practical implications suggest consistent communication of institutional goals, application of balanced leadership methods, optimization of workspace conditions, and implementation of recognition and reward systems to foster employee engagement, accountability, and effective service delivery.